IMPLEMENTASI METODE PEMBELAJARAN MIND MAPPING GUNA MENINGKATKAN MOTIVASI PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTs NEGERI 2 BLITAR - Lutfi Indah Nurjihananingrum; Dzulfikar Rodafi; Dwi Fitri Wiyono (VICRATINA, 2021)
At MTs Negeri 2 Blitar, an appropriate learning method was found to increase students' learning motivation during the pandemic, namely the mind mapping learning method. Mind mapping learning method is able to hone the left brain and right brain of students actively and synergistically, so as to overcome boredom in learning. The researcher acts as a human instrument. This research uses a qualitative approach, with the type of case study research. In collecting data, researchers used data triangulation techniques. The results of the study can be explained that the implementation of the mind mapping learning method on the subjects of aqidah morals class VIII is quite effective in increasing students' learning motivation. The response of students to the mind mapping method was very positive, marked by the increasing number of students who submitted assignments on time and had satisfactory work results. The implementation of the mind mapping method is said to be more interesting, fun, easy to understand, and easy to remember. Suggestions from researchers in making mind mapping use imagination and patience to get the best results. Patience and continuous practice are the keys to success in making a good mind map. Practice makes perfect.